Individual Choice when Objects have "Ordinal" Properties - Plott, Charles R.; Little, James T.; Parks, Robert P. (Review of Economic Studies, 1975)
We have attempted here to trace the implications, in terms of operational procedures, of some postulates about the "physical" nature of objects on one hand and individual choice behaviour on the other. We summarize the major result in very loose terms by asserting that if when choosing from among several objects which are characterized by "qualitative" or "ordinal" properties, an individual's choice obeys a transitivity law, then the choice is necessarily" dictated" by one characteristic a lone; that is, the underlying preference must be lexicographic in one of these ordinal properties. The reader must consult the text below for an elaboration on the meaning of the terms emphasized by quotation marks before the proper context of the result can be established.